Observation of type-II topological nodal-line fermions in ZrSiSe - Zhao, M; Zhuang, Z-Y; Wu, F; Leng, P; Joseph, NB; Xie, X; Ozerov, M; He, S; Chen, Y; Narayan, A; Liu, Z; Xiu, F (American Chemical Society, 2024)

(untitled)
Recently, there has been significant interest in topological nodal-line semimetals due to their linear energy dispersion with one-dimensional nodal lines or loops. These materials exhibit fascinating physical properties, such as drumhead surface states and 3D anisotropic nodal-line structures. Similar to Weyl semimetals, type-II nodal-line semimetals have two crossing bands that are both electron-like or hole-like along a certain direction. However, the direct observation of type-II nodal-line Fermions has been challenging due to the lack of suitable material platforms and the low density of states. Here we present experimental evidence for the coexistence of both type-I and type-II nodal-line Fermions in ZrSiSe, which was obtained through magneto-optical and angle-resolved photoemission spectroscopy (ARPES) measurements. Our density functional theory calculations predict that the type-II nodal-line structure can be developed in the Z-R line of the first Brillouin zone based on the lattice constants of the grown single crystal. Indeed, ARPES measurements reveal the type-II nodal-line band structure. The extracted type-II Landau level transitions from magneto-optical measurements exhibit good agreement with the calculated type-II energy dispersion model based on the band structure. Our experimental results demonstrate that ZrSiSe possesses two types of nodal-line Fermions, distinguishing it from other ZrSiX (X = S, Te) materials and positioning it as an ideal platform for investigating type-II nodal-line semimetals.